Heterogeneous disease and intermittent treatment in metastatic colorectal cancer: A case report - De Stefano, Alfonso; Zanaletti, Nicoletta; Cassata, Antonino; Silvestro, Lucrezia; Nappi, Anna; Casaretti, Rossana; Romano, Carmela; Foschini, Francesca; Cardone, Claudia; Borrelli, Marco; Petrillo, Antonella; Budillon, Alfredo; et al. (Frontiers in Oncology, 2023)
Background. Metastatic colorectal cancer is one of the most common causes of cancer death worldwide. RAS and BRAF mutational analyses are strongly recommended before beginning chemotherapy in the metastatic setting for their predictive role for the efficacy of anti-EGFR monoclonal antibodies. In most of cases, mutational status coincides between primary tumor and metastases. In RAS and BRAF wild-type patients treated with anti-EGFRs, after an induction treatment period, recent evidences support the role of a maintenance treatment with fluoropyrimidines and anti-EGFRs. However, skin toxicity is the most described and limiting side effect of maintenance. Moreover, it is described that the continuous administration of these monoclonal antibodies drives to an acquired resistance to anti-EGFRs, driving to treatment failure. Intermittent strategy with chemotherapy plus anti-EGFR may help maintain treatment efficacy, delaying resistance. Case Presentation. In this case report, we describe the case of a RAS-BRAF wild-type elderly patient, undergoing first-line chemotherapy with FOLFOX + panitumumab, reporting response of disease on all metastatic sites except for a node. This node, surgically removed, revealed to host BRAF V600 mutant clones. After surgery, patient continued chemotherapy with a stop-and-go strategy continuing to benefit from the same drugs after four years since diagnosis, continuing to achieve response when on treatment and avoiding unacceptable anti-EGFR toxicity. This patient, still alive after six years since the diagnosis, represents the case of a good synergy between molecular profiling of disease, surgery and intermittent treatment.